CHINESE PROPAGANDA IN RUSSIA: AESTHETIC ELEMENTS OF THE STRATEGY - SKRUDUPAS, ARŪNAS (Politologija, 2012)
Chinese propaganda in Russia is not easily noticeable against a background of real or alleged similarities between the countries, strategic partnerships and at least declared cooperation. However, the topicality of this research lies in the fact that both are large countries, big players on the international scene, and the weakening of Russia due to Sinification may have very serious consequences for the international geopolitical configuration and may therefore shape the nature of the processes taking place in it. When talking about Chinese propaganda in Russia, it needs to be agreed that the discussion is not so much about the future of the BRIC bloc system as about a G2 system (just USAand China), i.e. a bipolar international system and its potential to become unipolar in the near future with the Celestial Empire in the role of hegemonic player. The aim of the article is to analyse the aesthetic aspect of Chinese propaganda in Russia. Having regard to the multifaceted nature of the problem being analysed, an interdisciplinary approach was adopted, including linguistic, art studies and prognostic analysis methods. In the first part of the article an attempt is made: to analyse the ideas and concepts put forward by China in Russia on official internet (theoretical level of the concepts); to study the ways and means of putting forward those ideas and concepts, i.e. special characteristics and style of the language and the rhetoric used (linguistic level); to study the artistic visual aesthetics solutions used (visual level). In the second part of the article an attempt is made analyse the Russian reaction to Chinese propaganda: ideological and pragmatic Sinophilia (acceptance level) and Sinophobia (rejection level). In the third part of the article it is asserted that bearing in mind the current post-modern attitude that we humans are primates with basic exotic–erotic and emotional–visual orientation, in the spiritual realm Chinese propaganda manages to put forward the Chinese vision of aesthetics or aesthetic metaphysics as a substitute for religion. It is asserted that Confucianism and aesthetic metaphysics are not alternatives; rather they are complementary, resources of Chinese propaganda in Russia that reinforce one another. The article espouses the opinion that the Confucian level of Chinese propaganda in Russia is aimed more at the public, community sphere of social values, seeking to harmonise the leading values of Russian and Chinese society; or, more precisely, to encourage Russian values to slowly but surely adapt to Chinese values. Meanwhile, the aesthetic metaphysics content of Chinese propaganda is directed not at the public, social, community, civic sphere of values or the modelling of individual’s behaviour in regard of this projection, but rather at the individual, private, intimate, personal level. The article stresses that the external social sphere (Confucianism) and private personal life (aesthetics) could be said to immanently embody the holistic impetus that lies within humans to reconcile and harmonise ethics and aesthetics; however, this harmony is now written not so much in Cyrillic as in Chinese characters.To summarise, the article proposes the conclusion that Chinese propaganda in Russia is expressed at the direct/obvious pragmatic level for getting an effect on the formulation and execution of foreign policy as well as at the indirect/not-so-obvious level of passing on cultural and civilisational values, with respective orientation to short-term and long-term gains.The part of Chinese propaganda in Russia that seeks direct/external goals can be said to have been successful so far, since Russia maintains a basically benevolent diplomatic – strategic stance toward China. The success of non-obvious and deeper-reaching Chinese propaganda in Russia is more debatable. Nonetheless, there is a channel or space open to interaction, where Chinese aesthetic propaganda and Russian large-nation propaganda (which in a sense is also aesthetic) can meet and compete.